Incidence of Cannula-Associated Deep Vein Thrombosis After Veno-Venous Extracorporeal Membrane Oxygenation. Issue 5 (September 2017) - Menaker, Jay; Tabatabai, Ali; Rector, Raymond; Dolly, Katelyn; Kufera, Joseph; Lee, Eugenia; Kon, Zachary; Sanchez, Pablo; Pham, Si; Herr, Daniel L.; Mazzeffi, Michael; Rabinowitz, Ronald P.; et al.
Abstract : Limited literature regarding the incidence of cannula-associated deep vein thrombosis (CaDVT) after veno-venous extracorporeal membrane oxygenation (VV ECMO) exists. The purpose of this study was to identify the incidence of post decannulation CaDVT and identify any associated risk factors. Forty-eight patients were admitted between August 2014 and January 2016 to the Lung Rescue Unit were included in the study. Protocolized anticoagulation levels (partial thromboplastin time [PTT] 45–55 seconds) and routine post decannulation DVT screening were in place during the study period. Forty-one (85.4%) patients had CaDVT. Of those with CaDVT, 31 (76%) patients were treated with full anti-coagulation therapy. Thirty-four (76%) patients with right internal jugular (RIJ) cannulation had CaDVT at cannula site. Twenty-five (61%) patients had CaDVT in the lower extremity (18 associated right femoral vein cannulation and 7 left femoral vein cannulation). Eighteen (44%) patients had both upper and lower extremity CaDVT. Overall, patients with CaDVT tended to be older, have a higher body mass index (BMI), and on ECMO longer ( p = NS). Mean PTT during time on ECMO between patients that did and did not have CaDVT did not differ. No clinical evidence of pulmonary embolism (PE) was seen.